Internet Addiction and Its Association with Personality Traits and Depression in Medical Undergraduates, A Cross-Sectional Study from Pakistan: Internet Association with Personality Traits and Depression in Medical Undergraduates - Rashid, Farah; Zeeshan, Mehwish; Alsaidi, Nahla (Pakistan Journal of Health Sciences, 2024)
Internet usage has gained an essential role in modern-day life, leading to various undesirable behaviours. Unnecessary internet use can lead to dependence which poses significant mental health risks like depression and specific personality traits, particularly for university medical students, potentially impacting their education and future careers. Objectives: To examine Internet addiction among MBBS scholars and investigate the relationship between excessive internet use, depression, personality traits, and socio-demographic variables in this group. Methods: A cross-sectional survey was conducted with 206 medical undergraduates from the People’s University of Medical and Health Sciences for Women, Nawabshah, Pakistan through convenience sampling by self-administered questionnaire. The Young's Internet Addiction Test assessed Internet addiction, the Patient Health Questionnaire-9 measured depression, and the Ten-Item Personality Inventory and a self-structured questionnaire evaluated personality traits and socio-demographic characteristics respectively. Results: The mean age of the female medical students was 21.72 ± 1.631 years. The majority were Sindhi Muslims and unmarried. In 68.3% of the participants, mild internet addiction was found, with a mean score of 40.76 ± 16.495. Approximately half of the participants experienced depression. Participants with conscientiousness (Type 3) and emotional stability (Type 4) personalities were negatively associated with Internet addiction and positively associated with depression, particularly among second-year students. Conclusions: It was concluded that internet addiction is an alarming issue in medical students, leading to negative outcomes like depression, poor conscientiousness, and emotional stability. Efforts should be made to raise awareness and develop alternatives.